Development of Osborn Learning Model Based on Critical Creative and Character on Santri Pancasila Profile - Lanya, Harfin; Nuritasari, Fetty; Zayyadi, Moh; Saputra, Andi; Zahroh, Novita Dianatus (Universitas Nahdlatul Ulama Blitar, 2024)
This study aims to develop a 3C-based Osborn learning model to improve critical thinking skills, creativity, and character in students in a boarding school environment. The method used in this research is development research using the stages; 1) problem identification, 2) prototype and 3) assessment. The subjects in this study were MTs Az-Zubair students, especially class VII students. Problem identification is carried out by conducting learning observations conducted by teacher who teaches math subjects. Learning tools in the form of lesson plans (LIP), observation sheets, questionnaire sheets and formative test questions are developed to improve the 3C competence of students. The resulting device can be said to be good if it meets the criteria of valid, practical, and effective. The validity of the device can be tested by expert assessment, the practicality of the product can be tested by applying the model in learning and the effectiveness of the product can be tested by using the students' learning outcomes in answering formative questions. Based on the results of the study, it can be concluded that the device developed is valid, practical, and effective and can improve the critical thinking skills, creativity, and character of students.